Mapping criminological engagements within radicalization studies - Ahmad, Fahad (The British journal of criminology, 2019)
Radicalization theories positing a process towards violence are de rigueur in policy circles yet solicit mixed reactions within the academy. Attempting to build a more robust theory of radicalization, scholars have turned towards criminology. On the basis of a survey of literature where radicalization engages criminology, this article maps theories taken up to advance knowledge of radicalization as a process towards terrorist violence. The mapping exercise demonstrates a growing spectrum of criminological theories referenced by radicalization studies; however, these engagements have been selective: tending towards individualistic theories with limited (but recent) engagements with constructivist and structural theory. Contributing to critical interventions within the accelerating domains of theorizing radicalization to violence, we conclude that these engagements lack some of criminology’s broader reflexivity about its object of study.